2015
DOI: 10.1007/s10602-015-9202-6
|View full text |Cite
|
Sign up to set email alerts
|

EU enlargement and satisfaction with democracy: a peculiar case of immiserizing growth

Abstract: Studies on EU enlargement mostly focus on its welfare-economic and much less so on its public-choice dimension. Yet, the latter may be as important as the former when it comes to sustain integration. This paper aims at filling the gap by exploring theoretically and empirically how enlargement of multi-level systems like the EU affects satisfaction with democracy . In order to assess the effects of a widening in membership, we present a novel approach that draws on the probability of being outvoted. We find tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…Scholars have found that European integration strengthens national identities (Polyakova and Fligstein 2016) and leads to the politicization of 'Europe' in domestic politics (Hutter and Grande 2014;Kriesi 2016). However, to the best of our knowledge, only one publication has directly tackled the question whether more 'Europe' leads citizens to grow dissatisfied with (domestic) democracy: the work of Dluhosch et al (2016). Our work has much in common with that of Dluhosch et al (2016) -who examine whether EU enlargements decrease satisfaction with democracy.…”
Section: 'Europe' and Democratic Dissatisfactionmentioning
confidence: 94%
See 2 more Smart Citations
“…Scholars have found that European integration strengthens national identities (Polyakova and Fligstein 2016) and leads to the politicization of 'Europe' in domestic politics (Hutter and Grande 2014;Kriesi 2016). However, to the best of our knowledge, only one publication has directly tackled the question whether more 'Europe' leads citizens to grow dissatisfied with (domestic) democracy: the work of Dluhosch et al (2016). Our work has much in common with that of Dluhosch et al (2016) -who examine whether EU enlargements decrease satisfaction with democracy.…”
Section: 'Europe' and Democratic Dissatisfactionmentioning
confidence: 94%
“…However, to the best of our knowledge, only one publication has directly tackled the question whether more 'Europe' leads citizens to grow dissatisfied with (domestic) democracy: the work of Dluhosch et al (2016). Our work has much in common with that of Dluhosch et al (2016) -who examine whether EU enlargements decrease satisfaction with democracy. These authors also rely on data from the Eurobarometer surveys to study satisfaction with democracy, and they conclude that EU enlargement has negatively affected satisfaction with democracy.…”
Section: 'Europe' and Democratic Dissatisfactionmentioning
confidence: 99%
See 1 more Smart Citation